The Role of Breastfeeding in Preserving the Health of Mother and Child - Stefanović, Ljiljana (PONS - medicinski časopis, 2024)
Breastfeeding is the cornerstone of infant and young child survival, nutrition and development and maternal health. Many studies have shown thant women who breastfeed their children have ovarian or breastcarcinoma, cardiovascular diseases and diabetes type 2 rarely. Also, breastffeding is protective factor for postpartal depression, leads to faster weight loss after giving birth, faster return of the uterus, reduces possibility of postpartal hemorrhage. Breastfed children are more intelligent, less likely to develop autistic spectrum, less tendency to develop obesity and allergies, better immunity. At the time of the pandemic Covid 19, center of gravity of health systems of all countries was put on prevention and combat against new infective disease. Family care is neglected. The World Health Organization recommends exclusive breastfeeding for the first 6 months of life, followed by continued breastfeeding with appropriate complementary foods for up to 2 years and beyond. According data of World Health organization, in 2015-2021, the percent of infants under six months of age, exclusively breastfed reached 48%, ten percentage points higher than a decade earlier and close to the WHO target of 50% by 2025. The global target for 2030, however, is to reach 70%. Statistical data on the proportion of breastfed children and monitoring of breastfeeding rates in the Republic of Serbia still cannot be obtained from routine health statistics, although they are much needed. To compare and monitor breastfeeding rates, as well as for planning activities related to breastfeeding promotion, data is most often used from MISC, Multiple Indicator Cluster Survey. According to the latest data MISC-a, in the Republic of Serbia 90,4 % children were started breastfeeding, but only 12 % of children are exclusively breastfed unil the age of 6 months.